2015
DOI: 10.1002/pbc.25460
|View full text |Cite
|
Sign up to set email alerts
|

Influence of image‐defined risk factors on the outcome of patients with localised neuroblastoma. A report from the LNESG1 study of the European International Society of Paediatric Oncology Neuroblastoma Group

Abstract: BackgroundThe European multicenter study LNESG1 was designed to evaluate the safety and efficacy of surgical treatment alone in patients with localised neuroblastoma. In a retrospective, observational study we examined the impact of image‐defined risk factors (IDRF) on operative complications and survival (EFS and OS).Procedure534 patients with localised, non‐MYCN amplified neuroblastoma were recruited between 1995 and 1999. Group 1 consisted of 291 patients without IDRF (Stage L1 in the International Neurobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 20 publications
(37 reference statements)
1
37
1
2
Order By: Relevance
“…Therefore, we predicted that asymptomatic patients with GN and GNB‐I could be followed with observation to avoid surgical complications. IDRFs, which have been shown to predict surgical morbidities in localized NB, were detected in almost 40% of our patients and presence of an IDRF was associated with postoperative complications.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, we predicted that asymptomatic patients with GN and GNB‐I could be followed with observation to avoid surgical complications. IDRFs, which have been shown to predict surgical morbidities in localized NB, were detected in almost 40% of our patients and presence of an IDRF was associated with postoperative complications.…”
Section: Discussionmentioning
confidence: 84%
“…Surgical resection is a part of the multidisciplinary approach, for which it is important to decrease the general invasiveness and damage to the surrounding tissues and promptly transition to subsequent treatments [13]. Image-defined risk factors (IDRFs) are surgical risk factors that are evaluated according to the concepts established by the International Neuroblastoma Risk Group, as proposed by collaborative studies conducted in Europe [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, patients with IDRF in preoperative imaging may benefit from neoadjuvant chemotherapy. 13 Tumors exhibiting IDRF usually show a larger tumor volume, and therefore, the likelihood of a complete resection decreases with an increasing number of IDRF involved. This has been reported by Günther et al, who described in their case series with 60 patients (with abdominal NB) a significant negative correlation between the total amount of IDRF and the likelihood of radical tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports about abdominal NB describe a relationship between IDRF and larger tumor volumes and intraoperative complications. 13,[17][18][19] For instance, a large retrospective study in 534 NB patients demonstrated significantly more perioperative complications in IDRF-positive patients than in study participants without (L1). 13 The current literature regarding neurovascular complications after pelvic NB resection suggests a prevalence of 15 to 35%.…”
Section: Discussionmentioning
confidence: 99%